Aldol reactions of 1, 2-diketones catalyzed by amines to afford furanose derivatives. Issue 5 (28th January 2015) - Jithender, Enukonda; Katsuyama, Isamu; Zhang, Dongxin; Johnson, Sherida; Tanaka, Fujie
Graphical abstract: Abstract: Molecules with furanose units are often bioactive. To concisely synthesize these molecules, we have developed aldol reactions of 1, 2-diketones that afford furanose derivatives in one pot. For these reactions with the use of N, N ′-diisopropylethylamine as catalyst, aldol products were obtained via C–C bond formation at the internal methylene carbon of the acetyl alkyl ketone derivatives. Regioselectivities of the reactions depended on the catalyst. The aldol products from the reactions with aldehydes in which the C–C bond formation occurred at the internal methylene carbon of the acetyl alkyl ketone derivatives were easily air-oxidized to afford the corresponding 2-hydroxy-2 H -furanone derivatives.